Cerebellar connections to the rostral reticular nucleus of the thalamus in the rat - ONAT, FİLİZ; YANANLI, HASAN RACİ; ŞEHİRLİ, ÜMİT SÜLEYMAN (WILEY, 2002)
We studied the cerebellar connections to the reticular nucleus thalamus (RNT) by means of retrograde axonal transport of horseradish peroxidase (HRP) in the rat. Specific HRP pressure injections to the rostral RNT(1.6-1.8 mm caudal to bregma) resulted in retrograde labelling of neurones in the cerebellar nuclei. The rostral RNT showed specific topographical organization of its cerebellar connections. Microinjections into the rostral RNT, 1.6 mm caudal to bregma, produced numerous HRP-labelled neurones within the anterior interposed (emboliform nucleus) and scarce HRP-labelled neurones within the lateral (dentate nucleus) cerebellar nuclei, whereas injections into the rostral RNT, 1.8 mm caudal to bregma, produced numerous HRP-labelled neurones within the posterior interposed (globose nucleus) and scarce lightly HRP-labelled neurones within the lateral (dentate nucleus) cerebellar nuclei. Cerebellar connections with the rostral RNT were exclusively ipsilateral to the injection site. No HRP-labelled cells were detected in the medial (fastigial nucleus) cerebellar nucleus. The cerebellar connections reach the RNT via the superior cerebellar peduncle. By contrast, HRP injections into the anterior, posterior interposed and lateral cerebellar nuclei produced no labelled cells within the RNT. This study demonstrates the existence of direct cerebello-RNT but not RNT-cerebellar connections. The presence of the cerebello-RNT connections introduces a new route through which the cerebellum may influence RNT and thus cerebral cortical activity.
Keywords: cerebellum; connections; nucleus reticularis thalami; rat; HORSERADISH-PEROXIDASE; FASTIGIAL NUCLEUS; ORGANIZATION; PROJECTIONS; HYPOTHALAMUS; STIMULATION; NEURONS; COMPLEX; MACAQUE; SECTOR